Manejo Integrado del Orozco (Phyllophaga spp.) en el cultivo de café (Coffea arabica)” en la Hacienda Chojampe, Cantón Ventanas - Fuentes Vera, Jenniffer Taymy (2020)
Coffee is a perennial cycle tree that adapts to tropical climates, it is native to Africa and for many countries it is one of the main crops of economic importance such as Brazil, however, in Ecuador currently the rate of coffee production it is very limited. Ecuador has a great capacity as a coffee producer, and is considered one of the few countries in the world that exports all the varieties of coffee, among which washed Arabica, natural Arabica and Robusta are mentioned. Economically, it constitutes a source of foreign exchange and income for the actors in the coffee chains. Socially, many ethnic groups and peoples are involved in coffee chains in 23 of the 24 provinces of Ecuador, dispersed in a wide social fabric. Coffee cultivation is susceptible to climatic changes, nutrient deficiencies and the incidence of pests, among which Orozco is a pest that causes considerable damage to various crops and in many cases total loss of production, therefore it is found in coffee destroying the root system, in its larval stage and its symptoms is observed in the leaf area. Therefore, prevention measures are through biological control through the use of fungi of the genus Metarhizium sp. The main objective was to determine the management integration of Orozco (Phyllophaga spp.) in coffee cultivation (Coffea arabica) ”at the Chojampe farm. This study was analyzed at the Chojampe coffee farm, which is located in the Los Ríos province of the Ventanas canton. The research obtained is supported by information and questions presented by the technicians of Chojampe farm. Chojampe coffee producing farm was visited, where information was obtained on Orozco considered one of the insects that causes damage to the roots, interfering with plant development and long-term production. The technicians of the farm recommend as a physical control the placement of white light traps at points near the cultivation lots, which will gradually reduce the populations of Orozco